Ayush Medicine In Indian Society - Dr. Mamidi Nandan Balajee (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Ayush comprises of Ayurveda, Yoga& Naturopathy Unani, Siddha, Sow Rigpa and Homoeopathy. In our society Grandma’s remedies play an active role in the initial phase of any ailment. Our kitchen comprises many items which are directly or indirectly related to our health. Our customs and beliefs keep us in touch with Mother Nature and her components. Allopathic Medicine got impetus in the colonial rule and Ayush System was pushed back. After independence Indian Systems of Medicine and Homoeopathy got legality but the pace was slow. This paper intends to study the present-day scenario of the Ayush in our society.
Keywords: Medicine; Homoeopathy; NSSO; Awareness